The Impact of a Training Program Built on Learning Technology on Developing the Skills to Deal with Autistic Children Behavior in the Center of Sulaymaniyah Governorate - Araz Hakem Radha; Renas Babakr Khdir (Zanco Journal of Humanity Sciences)
The current of reserach aims to identify: the effectiveness of a training program based on mobile learning technology in developing the skills to deal with autistic children behavior n in the center of Sulaymaniyah Governorate. This was done by verifying the validity of the following hypotheses: There are no statistically significant differences at the level of significance (0.05) between the mean scores of the experimental group members in developing the skills to deal with autistic children behavior before and after the application of the training program. And the training program does not achieve its effectiveness in developing the skills to deal with autistic children behavior with members of the experimental group.